Similarities between clinically matched and unmatched analogue patient raters: a mixed methods study: Presenter(s): Angelo D'Addario, National Board of Medical Examiners, United States. (April 2023) - King, Ann; Mazor, Kathleen; Houriet, Andrew; Musselman, Thea; Hoppe, Ruth
Abstract : Background: Analogue patients (AP) are recognized as valuable in evaluating physician-patient communication. Most studies using APs have had minimal inclusion criteria, such that they have not been selected to necessarily match the clinical characteristics of the patient in the situation they are evaluating. This study sought to examine whether clinically matched and unmatched APs provided similar ratings and identify similar behaviors as important. Method: Twenty-six physicians provided audio responses to two patient communication vignettes. One vignette depicted a patient with a cancer diagnosis and the other with an overweight diagnosis. Twenty clinically matched and 103 unmatched APs were recruited to rate responses and provide feedback in response to an open-ended question on how they would have wanted the physician to respond. Mean ratings were computed for each physician response for both matched and unmatched APs and Pearson correlations were used to determine their relationship. Matched AP open-ended responses were analyzed using thematic analysis. A naïve analyst coded unmatched AP responses using themes gathered from matched AP responses to examine similarities in desired physician behavior. Findings: Clinically matched and unmatched AP ratings of physician communication skills were significantly correlated for both vignettes, r(24) = 0.88, p<.0001 and r(24) = 0.83, p<.0001. Twenty-one themes were developed from matched AP responses. Examples of themes are "provide realistic hope" for the cancer vignette and "explore the patient's life situation that may contribute to or trigger weight gain" for the overweight vignette. All codable unmatched AP responses fit at least 1 theme derived from matched APs. No themes emerged from unmatched AP responses that couldn't be coded with, or were contradictory of, clinically matched themes. Discussion: When clinically matched AP are difficult to attain, clinically unmatched APs may serve as adequate surrogates to rate physician communication skills and provide feedback.